동질 사배체 탱자에서 염색체 배가와 수체 표현형의 변이 - 김샛별(Sat-Byul Kim); Jian Liang Lu; 윤수현(Su-Hyun Yun); 고상욱(Sang-Wook Koh); 송관정(Kwan Jeong Song); 오은의(Eun Ui Oh); 채치원(Chi-Won Chae) (Weon'ye gwahag gi'sulji, 2014)
The study was conducted to investigate the possibility that epigenetic DNA methylation causes tree phenotypic variation in autotetraploids through evaluating the phenotypic variation and DNA methylation in autotetraploids occurred spontaneously from diploid trifoliate orange. Chromosome analysis confirmed that fourteen trifoliate orange trees of selected by flow cytometry were tetraploids (2n = 4X = 36) without any aneuploids. Chromomycin A3 staining determined that these trees were all autotetraploid with doubled chromosome set. Tree phenotypes, such as tree height and width, branching number, length, and angle, internode length, and leaf characteristics, varied in the autotetraploids. Chlorophyll indices were diverse in the autotetraploids, but photosynthetic rates were not significantly different. In addition, a wide range of variation was observed in stomatal density and guard cell length. Analysis of global cytosine DNA methylation showed that there was a variation of the methylation level in autotetraploids. More than half of 14 autotetraploids had at least 2 times higher methylation level than diploid trifoliate orange. The results indicate that tree phenotypic variation in autotetraploids might be related to global DNA methylation for reducing gene redundancy. 이배체 탱자로부터 자연적으로 발생한 동질 사배체 탱자의 수체 형질 관련 표현형 및 유전체 메틸화 변이 정도를 분석하여 후성 유전의 하나인 유전체 메틸화가 동질 사배체의 표현형 변이의 요인으로 작용할 수 있음을 구명하고자 본 실험을 수행하였다. 이배체 탱자에서 유래된 14주의 사배체 탱자로부터 염색체를 분석하여 이수성이 없는 2n = 4X = 36 식물체로 확인하였다. CMA 핵형 분석 결과 염색체가 배가된 동질 사배체임을 확인할 수 있었다. 동질 사배체에서 수고, 수폭, 원가지 수, 원가지 길이, 분지 각도, 마디 길이, 잎의 특성 등 동질 사배체 수체 표현형에 있어서 상당한 변이가 나타남을 확인하였다. 또한 동질 사배체 광합성률에는 큰 차이는 없었지만, SPAD 값에 의한 엽록소 지수에 있어서도 표현형이 다양하게 나타나는 것을 알 수 있었다. 그 외에도 기공 밀도와 공변 세포 길이에 있어서 광범위하게 변이가 관찰되는 것을 알 수 있었다. Global cytosine DNA 메틸화를 분석한 결과 개체 간 메틸화 정도에 차이가 존재함을 알 수 있었다. 동질 사배체 탱자 14주의 절반이 이배체 탱자의 메틸화와 비교하였을 때 2배 이상으로 나타난 것을 확인하였다. 본 연구 결과 동질 사배체에서 나타나는 수체형질 변이가 gene redundency를 줄이기 위한 global cytosine DNA 메틸화와 관계될 수 있음을 확인하였다.